USING PREDICT LOCATE ADD NOTE (PLAN) STRATEGY IN TEACHING READING REPORT TEXTS TO SENIOR HIGH SCHOOL STUDENTS - Fastilla Fastilla; Zainuddin Amir (Universitas Negeri Padang, 2012)
This article discusses use of PLAN Strategy in teaching reading report text to senior high school students. PLAN is a reading strategy that helps readers to read actively and strategically. In implementing this strategy, there are four main steps to be followed. First, the students predict the information they are going to find from the text and transform the prediction into a concept map (Predict). Then, the students identify the information in the map by placing checkmark next to known or familiar information and question mark next to unknown information (Locate). After that, the students read the text to correct the prediction (Add). Finally, the students complete relevant tasks to check their comprehension (Note). Abstrak Artikel ini membahas penggunaan strategi membaca PLAN dalam mengajar membaca teks report. PLAN adalah suatu strategi membaca yang dapat membantu siswa membaca teks secara aktif dan strategis. Dalam mengaplikasikan strategi ini, ada empat langkah kegiatan membaca yang harus diikuti. Pertama, siswa memprediksi informasi yang akan yang akan didapat dari teks kemudian menuangkannya ke dalam peta konsep (Predict). Lalu, siswa mengidentifikasi informasi pada peta konsep dengan cara memberi tanda centang disamping informasi yang diketahui dan tanda tanya disamping informasi yang kurang atau tidak diketahui (Locate). Setelah itu, siswa membaca teks sambil mengoreksi prediksi yang telah dibuat (Add). Terakhir, siswa mengerjakan tugas-tugas yang relevan untuk mengecek pemahaman mereka (Note).